The art and science of natural dyes : principles, experiments, and results - Boutrup, Joy; Ellis, Catharine, 1951- (Atglen, Pa. : Schiffer Books, 2018)
"This long-awaited guide serves as a tool to explain the general principles of natural dyeing, and to help dyers to become more accomplished at their craft through an increased understanding of the process. Photos of more than 450 samples demonstrate the results of actual dye tests, and detailed information covers every aspect of natural dyeing including theory, fibers, mordants, dyes, printing, organic indigo vats, finishing, and the evaluation of dye fastness. Special techniques of printing and discharging indigo are featured as well. The book is intended for dyers and printers who wish to more completely understand the "why" and the "how," while ensuring safe and sustainable practices. Written by a textile engineer and chemist (Boutrup) and a textile artist and practitioner (Ellis), its detailed and tested recipes for every process, including charts and comparisons, make it the ideal resource for dyers with all levels of experience." -- Publisher's description
Dyeing textiles -- Fibers -- Dyes -- Mordants -- Immersion dyeing -- Indigo -- Mixing and shading colors -- Printing -- Finishing of dyed and printed textiles -- Dye fastness -- Recipes.
Includes bibliographical references (page 174) and index.
Keywords: Dye plants; Dyes and dyeing -- Chemistry; Natural products